Керамічні клейма з поселення Віліне (Розсадне) — у періодизації та хронології пам’ятки (південно-західний Крим) - Медведєв, Г.В. (Археологія і давня історія України, 2021)
Стаття присвячена публікації аморфних клейм, виявлених у 2008—2014 рр. при дослідженні поселення Віліно (Розсадне). Клейма представлені такими центрами як Синопа, Херсонес, Родос, також визначені їх дати. На пам’ятці, простежено чотири будівельні періоди (A—D) — два античних і два пізньоскіфських. Клейма, разом з іншими археологічними знахідками, є важливими хроноіндикаторами поселенської структури в системі хори Херсонеса та Західного Криму. This paper is devoted to the publication of amphora stamps discovered during excavation at the settlement of Vilino (Rassadnoe) in 2008—2014. During the research of the settlement the eastern border of the ancient estate and the main chronological framework of the settlement life were ascertained. The stone monumental structure was discovered in 2008. This is the cistern for collecting and storage of rainwater. In the Late Scythian time it was used as a burial structure (crypt). Ceramic stamps found at the site are represented by such centers as Sinopa, Chersonesos, Rhodes. Unfortunately not all of them were discovered in the cultural layers (in situ) and some were found in disturbed layers, at the surface or in the looter’s holes. Nevertheless, with a lesser or greater degree of probability, it’s possible to correlate them with the chronology of the settlement and periods of its life. On the excavated areas of the site four building periods (A—D) were observed — two Classic and two Late Scythian. The first period is associated with the time of activity of the Greek fortified estate (Chersonesos Сhora) from the last quarter of the 4th to the early 3rd century BC. In the second period, after a break, the population has come back to the settlement in the last quarter of the 3rd century BC. There was the period of recolonization during which the restructuring of the settlement has carried out. At the end of the first quarter of the 2nd century BC the life at the settlement was stopped. The next two periods correspond to the Late Scythian culture. However, the layers and building remains of the late 2nd century BC — 1st century AD was destroyed by plowing and looter’s holes. The upper horizon of the settlement contains the material from the 1st—3rd centuries AD. The stamps and other archaeological material are important chronological indicators of the archaeological site in the system of the Chora of Chersonesos and in the whole Western Crimea.